The role of timeliness in the cost-effectiveness of older adult vaccination: A case study of pneumococcal conjugate vaccine in Australia. Issue 10 (28th February 2018) - Chen, C.; Wood, J.G.; Beutels, P.; Menzies, R.; MacIntyre, C.R.; Dirmesropian, S.; Reyes, J.F.; McIntyre, P.; Newall, A.T.
Abstract: While the impact of the timeliness of vaccine administration has been well-studied for childhood vaccinations, there has been little detailed quantitative analysis on the potential impact of the timeliness of vaccinations in older adults. The aim of this study was to explore the impact of implementing more realistic observed uptake distributions, taking into the account reduced vaccine efficacy but higher pneumococcal disease burden with increasing age beyond 65 years. A multi-cohort Markov model was constructed to evaluate the cost-effectiveness of a pneumococcal (PCV13) immunisation program in Australia, assuming two different uptake modelling approaches. The approach using an estimate of observed uptake was compared with a scenario in which the total cumulative uptake was delivered at the recommended age of vaccination. We found these two approaches produced different results both in terms of cases prevented and cost-effectiveness. The impact of the non-timely uptake in adult programs may sometimes have positive and other times negative effects, depending on several factors including the age-specific disease rates and the duration of vaccine protection. Our study highlights the importance of using realistic assumptions around uptake (including non-timely vaccination) when estimating the impact of vaccination in adults.